2020
DOI: 10.1186/s13071-020-04106-1
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii infection in slaughtered pigs and cattle in Poland: seroprevalence, molecular detection and characterization of parasites in meat

Abstract: Background Toxoplasma gondii infection may pose a severe medical problem especially in a congenital form and as an acquired infection in immunocompromised persons. Raw and undercooked meat of slaughtered animals is regarded as an important source of parasite infection; however, data concerning this issue in Poland are still insufficient. The aim of this study was to estimate the prevalence of T. gondii infection in pigs and cattle slaughtered for human consumption in Poland using serological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 56 publications
(75 reference statements)
0
8
0
2
Order By: Relevance
“…Unfortunately, foodborne parasites remain neglected compared with bacterial and viral pathogens [3]. Therefore, studies in this field, like epidemiological surveys [5,6], development of novel diagnostic tools [7][8][9], drug discovery [10], or investigation of pathogenicity [11], are particularly valuable.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, foodborne parasites remain neglected compared with bacterial and viral pathogens [3]. Therefore, studies in this field, like epidemiological surveys [5,6], development of novel diagnostic tools [7][8][9], drug discovery [10], or investigation of pathogenicity [11], are particularly valuable.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally-infected sows have been found to produce IgG class antibodies within two to three weeks of infection, and these antibodies remained for at least 38 weeks [ 52 ]. In pigs, the presence of anti- T. gondii antibodies correlates with the presence of parasite tissue cysts in the muscle tissue [ 11 , 12 , 28 , 30 ]; this has been confirmed by comparing seroprevalence with a bioassay confirming or excluding the presence of infective tissue cysts [ 36 ]. Elsewhere, Hill et al [ 53 ] found ELISA analysis of pig serum samples to demonstrate a 100% match with cat bioassay results; they also found MAT (Modified Agglutination Test) on the serum samples to demonstrate 80.64% match and ELISA on meat juice samples to demonstrate a 76.9% match.…”
Section: Discussionmentioning
confidence: 97%
“…Among these species, pigs (pork) are considered to be one of the main sources of meat-borne infection [ 27 ]. As it is not possible to detect T. gondii tissue cysts during routine post-mortem examination [ 28 ], the EFSA recommends the use of serological tests to detect specific antibodies when testing pigs [ 29 ], as this can indicate presence of tissue cysts in muscles [ 12 , 28 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…wyniki badań prowadzonych na fermach świń w Holandii, które wykazały, że drobne gryzonie przypadkowo zjadane przez świnie znacznie przyczyniają się do rozpowszechnienia zarażenia tym pasożytem na fermie [2]. W Polsce odsetek świń zarażonych T. gondii ocenia się na ok. 11% [4]. Wyniki badań oparte na analizie ryzyka wskazują na surowe mięso i surowe produkty mięsne jako najczęstsze źródła inwazji T. gondii ludzi w Europie [5].…”
Section: Wprowadzenieunclassified